Cannabidiol Induces Apoptosis and Perturbs Mitochondrial Function in Human and Canine Glioma Cells - Gross, Chase; Ramirez, Dominique A.; McGrath, Stephanie; Gustafson, Daniel L. (Frontiers in Pharmacology, 2021)
Cannabidiol (CBD), the major non-psychoactive compound found in cannabis, is frequently used both as a nutraceutical and therapeutic. Despite anecdotal evidence as an anticancer agent, little is known about the effect CBD has on cancer cells. Given the intractability and poor prognoses of brain cancers in human and veterinary medicine, we sought to characterize the in vitro cytotoxicity of CBD on human and canine gliomas. Glioma cells treated with CBD showed a range of cytotoxicity from 4.9-8.2 g/mL; canine cells appeared to be more sensitive than human. Treatment with >5 g/mL CBD invariably produced large cytosolic vesicles. The mode of cell death was then interrogated using pharmacologic inhibitors. Inhibition of apoptosis was sufficient to rescue CBD-mediated cytotoxicity. Inhibition of RIPK3, a classical necroptosis kinase, also rescued cells from death and prevented the formation of the large cytosolic vesicles. Next, cellular mitochondrial activity in the presence of CBD was assessed and within two hours of treatment CBD reduced oxygen consumption in a dose dependent manner with almost complete ablation of activity at 10 g/mL CBD. Fluorescent imaging with a mitochondrial-specific dye revealed that the large cytosolic vesicles were, in fact, swollen mitochondria. Lastly, calcium channels were pharmacologically inhibited and the effect on cell death was determined. Inhibition of mitochondrial channel VDAC1, but not the TRPV1 channel, rescued cells from CBD-mediated cytotoxicity. These results demonstrate the cytotoxic nature of CBD in human and canine glioma cells and suggest a mechanism of action involving dysregulation of calcium homeostasis and mitochondrial activity.